Controlling placement of nonspherical (boomerang) colloids in nematic cells with photopatterned director. (10th November 2016) - Peng, Chenhui; Turiv, Taras; Zhang, Rui; Guo, Yubing; Shiyanovskii, Sergij V; Wei, Qi-Huo; de Pablo, Juan; Lavrentovich, Oleg D
Abstract: Placing colloidal particles in predesigned sites represents a major challenge of the current state-of-the-art colloidal science. Nematic liquid crystals with spatially varying director patterns represent a promising approach to achieve a well-controlled placement of colloidal particles thanks to the elastic forces between the particles and the surrounding landscape of molecular orientation. Here we demonstrate how the spatially varying director field can be used to control placement of non-spherical particles of boomerang shape. The boomerang colloids create director distortions of a dipolar symmetry. When a boomerang particle is placed in a periodic splay-bend director pattern, it migrates towards the region of a maximum bend. The behavior is contrasted to that one of spherical particles with normal surface anchoring, which also produce dipolar director distortions, but prefer to compartmentalize into the regions with a maximum splay. The splay-bend periodic landscape thus allows one to spatially separate these two types of particles. By exploring overdamped dynamics of the colloids, we determine elastic driving forces responsible for the preferential placement. Control of colloidal locations through patterned molecular orientation can be explored for future applications in microfluidic, lab on a chip, sensing and sorting devices.